Exploring the relationship of declarative tactical knowledge with participation, football competence, and potentiality in a professional club (Real Sociedad) - Sánchez-López, R.; Echeazarra, I.; Arrieta, J. M.; Castellano, J. (Journal of Sport & Exercise Psychology, 2024)
We compared the declarative tactical knowledge (DTK) of 196 male and female players (16.9 ± 2.4 years) belonging to the academy of a Spanish professional football club with their participation (minutes played), football competence (coaching staff assessment), and future potential (technical direction prediction). The DTK had no correlation with the minutes played (%) by the participants during the 2021-22 season (r = -.162, p = .045). Student`s t test for independent samples compared the football competence of the participants with high DTK (n = 74) and low DTK (n = 76), proving a small impact (p = .021, d = 0.39) in favor of the first group. Although the high-DTK group showed a better average of potentiality, the technical direction identified more potential players for the first team in the low-DTK group. In conclusion, no solid evidence was found to justify that participants with higher DTK in each team were those who played more minutes and showed greater football competence and potentiality.